2023
DOI: 10.18502/ijph.v52i11.14025
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Cancer: Epidemiology, Etiology, and Prevention: A Narrative Review

Nurbek Igissin,
Vera Zatonskikh,
Zhansaya Telmanova
et al.

Abstract: Laryngeal cancer comprises 30%-40% of head and neck malignancies, and it is the most common malignancy in otolaryngology. The main risk factors for laryngeal cancer are tobacco use, excessive alcohol consumption, gastroesophageal reflex, Plummer-Vinson syndrome, exposure to heat, chemicals, and some viral infections. This literature review summarizes all known data over the past decade with an assessment of the main etiological factors related to cancer incidence, general measurement issues in the cancer epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Laryngeal cancer accounts for 30-40% of all head and neck malignancies and continues to impose a major burden on healthcare and society due to its significant impact on quality of life, morbidity and mortality. Although it has previously been demonstrated that mortality from this malignancy has declined in many developed countries in recent decades [10,11], COVID-19 may have reversed this positive trend for a variety of reasons other than for the direct interplay of SARS-CoV-2 with the host immune system, including disruption of cancer screening and diagnosis, deferred or even discontinued treatments, surveillance and follow-up, and impeded access to clinical trials and innovative therapies [12]. The most obvious consequence is the delayed detection of some cancers and the diagnosis of some malignancies at a more advanced stage than in the pre-pandemic period [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal cancer accounts for 30-40% of all head and neck malignancies and continues to impose a major burden on healthcare and society due to its significant impact on quality of life, morbidity and mortality. Although it has previously been demonstrated that mortality from this malignancy has declined in many developed countries in recent decades [10,11], COVID-19 may have reversed this positive trend for a variety of reasons other than for the direct interplay of SARS-CoV-2 with the host immune system, including disruption of cancer screening and diagnosis, deferred or even discontinued treatments, surveillance and follow-up, and impeded access to clinical trials and innovative therapies [12]. The most obvious consequence is the delayed detection of some cancers and the diagnosis of some malignancies at a more advanced stage than in the pre-pandemic period [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal cancer represents 30-40% of head and neck malignancies [1]. According to the latest available data, in 2020, there were approximately 185,000 new cases of laryngeal carcinoma worldwide, and the disease was responsible for 99,840 deaths [2].…”
Section: Introductionmentioning
confidence: 99%
“…While the need for endoscopic screening of high-risk and symptomatic individuals is clear, the medical community has not established routine laryngeal cancer screening guidelines for the wider population. 1 Flexible laryngoscopy is the primary diagnostic tool used to identify laryngeal disease. It is non-invasive, costeffective, and is typically performed in the outpatient clinic.…”
Section: Introductionmentioning
confidence: 99%
“…While the need for endoscopic screening of high-risk and symptomatic individuals is clear, the medical community has not established routine laryngeal cancer screening guidelines for the wider population. 1…”
Section: Introductionmentioning
confidence: 99%